RANCANGAN LEAN PRODUCTION DENGAN MENGGUNAKAN VALUE STREAM ANALYSIS TOOLS (VALSAT) UNTUK ELIMINASI WASTE DOMINAN & MENINGKATKAN PRODUKTIVITAS SISTEM PRODUKSI Studi Kasus: CV. Sogan Batik Rejodani - Dhuha Khanif Rizky; M. Ridwan Andi Purnomo; Nashrullah Setiawan (Teknoin, 2016)
With increasing competition in the industry, SMEs are required to be able to do continuous improvement to improve its performance so as to compete with other SMEs and able to apply the concept of lean production. In CV SBR, demand will increase in Ramadan. With the increase in orders, then the CV SBR required to continue to meet customer demand in a timely manner in accordance consumer expectations. This research will try to apply the concept of lean production by using value stream mapping and analysis of waste using the Value Stream Analysis Tools (VALSAT) in order to increase the productivity of the production system in the CV Sogan Batik Rejodani. The purpose of this study is to determine the percentage of Value Added, Non-Value Added, and Necessary but Non-Value Added Activity of batik production system. Furthermore, to determine the design of future state value stream mapping in CV SBR. Obtained results are given in the form of proposed improvements that can reduce the Non-Value Added Activity from 43% to 13%. In addition the draft future state value stream mapping can reduce cycle time from 16115.88 seconds to 15062.96 seconds and can reduce the lead time from 24589,028 seconds to 15932.62 seconds. With the reduction in value-added activity, it can increase the output of the product in a day so that the productivity of the production system increases.